Spending on farms ripples into the region: agritourism impacts - Dhungana, Purushottam; Khanal, Aditya R. (Frontiers in Environmental Economics, 2023)
Agritourism is gaining popularity throughout the United States and is important part of rural and regional development. However, the economic contributions from the agritourism, interface of agriculture and tourism, has received limited attention in regional impact estimation studies. This study estimates the regional economic impact of visitor spending in agritourism farms in Tennessee, using the data collected from sampled farms in Tennessee and secondary industry-level data. Economic impacts in terms of direct, indirect, and induced are estimated based on economic input-output modeling application (IMPLAN) and the social accounting matrix framework. We find that an estimated $65 million from visitors’ direct spending in agritourism farms contributes to the total industry output of $118.54 million in Tennessee. Additionally, we presented total value added, jobs created, labor incomes, and taxes generated through direct, indirect, and induced effects attributable to visitors’ spending in agritourism farms. Our findings indicate that the expansion of agritourism could bring economic development at both farm-level and state levels, particularly in the states like Tennessee where agriculture is an important industry and tourism is expanding.